Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
y = x² + x - 42
x² + x - 42
x = -1 +/- √(1² - 4(1)(-42))
2(1)
x = -1 +/- √(1 + 168)
2
x = -1 +/- √169
2
x = -1 +/- 13
2
x = -1 + 13 x = -1 - 13
2 2
x = 10 x = -14
2 2
x = 5 x = -7
-----------------------------------------------------------------------------------------------
y = x² + x - 42 y = x² + x - 42
y = (5)² + 5 - 42 y = (-7)² + 5 - 42
y = 25 + 5 - 42 y = 49 + 5 - 42
y = 30 - 42 y = 54 - 42
y = -12 y = 12
(x, y) = (5, -12) y = (-7, 12)
x² + x - 42
x = -1 +/- √(1² - 4(1)(-42))
2(1)
x = -1 +/- √(1 + 168)
2
x = -1 +/- √169
2
x = -1 +/- 13
2
x = -1 + 13 x = -1 - 13
2 2
x = 10 x = -14
2 2
x = 5 x = -7
-----------------------------------------------------------------------------------------------
y = x² + x - 42 y = x² + x - 42
y = (5)² + 5 - 42 y = (-7)² + 5 - 42
y = 25 + 5 - 42 y = 49 + 5 - 42
y = 30 - 42 y = 54 - 42
y = -12 y = 12
(x, y) = (5, -12) y = (-7, 12)
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.